Influence of solids and hydraulic retention times on microbial diversity and removal of estrogens and nonylphenols in a pilot-scale activated sludge plant - Mensah, Lawson; Petrie, Bruce; Scrimshaw, Mark; Cartmell, Elise; Fletton, Mandy; Campo Moreno, Pablo (Elsevier, 2023)
The removal of EDCs in activated sludge processes can be enhanced by increasing solid and hydraulic retention times (SRT and HRT); it has been suggested that the improvement in removal is due to changes in microbial community structure (MCS). Though the influence of SRT and HRT on chemical removal and MCS has been studied in isolation, their synergistic impact on MCS and the removal of estrogens and nonylphenols in activated sludge remains unknown. Hence, we investigated how both parameters influence MCS in activated sludge processes and their ulterior effect on EDC removal. In our study, an activated sludge pilot-plant was fed with domestic sewage fortified with 100 and 1000 ng/L nonylphenols or 2 and 15 ng/L estrogens and operated at 3, 10 and 27 d SRT (constant HRT) and at 8, 16 and 24 h HRT (constant SRT). The MCS was assessed by phospholipid fatty acids (PLFA) analysis, and the archaeal and bacterial diversities were determined by 16S rRNA analysis. From the PLFA, the microbial abundance ranked as follows: Gram-negative > fungi > Gram-positive > actinomycetes whilst 16S rRNA analysis revealed Proteobacteria > Bacteroidetes > Others. Both PLFA and 16S rRNA analysis detected changes in MCS as SRT and HRT were increased. An SRT increment from 3 to 10 d resulted in higher estrone (E1) removal from 19 to 93% and nonylphenol-4-exthoxylate (NP4EO) from 44 to 73%. These findings demonstrate that EDC-removal in activated sludge plants can be optimised where longer SRT (>10 d) and HRT (>8 h) are suitable. We have also demonstrated that PLFA can be used for routine monitoring of changes in MCS in activated sludge plants.
Keywords: Microbial diversity; Phospholipids fatty acids; 16S rRNA analysis; Estrogens; Nonylphenols; Activated sludge plant